2011
DOI: 10.4062/biomolther.2011.19.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacokinetics of Simvastatin and Its Pharmacologically Active Metabolite from Controlled-Release Tablets of Simvastatin in Rodent and Canine Animal Models

Abstract: a These two authors equally contributed to this work.Received Oct 1, 2010 Revised Nov 1, 2010 (Duggan et al., 1989;Bradford et al., 1991;Nishio et al., 2005). It was also reported that higher incidences of adverse events are associated with higher drug concentrations of statins and the most serious adverse events associated with them are hepatotoxicity and myotoxicity (Duggan et al., 1989;Vickers et al., 1990a;Bradford et al., 1991;McClelland et al., 1991). Since, SA has the similar mechanism of action lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For instance, in humans, pitavastatin has high bioavailability and a long half-life, while in dogs, pitavastatin has relatively high bioavailability, but its half-life is similar to that of other statins. 21,[29][30][31] Therefore, it remains unclear whether the present results reflect the efficacy of statins against tumours in vivo, hence further in vivo investigations remain warranted to elucidate the most effective statin in dogs.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, in humans, pitavastatin has high bioavailability and a long half-life, while in dogs, pitavastatin has relatively high bioavailability, but its half-life is similar to that of other statins. 21,[29][30][31] Therefore, it remains unclear whether the present results reflect the efficacy of statins against tumours in vivo, hence further in vivo investigations remain warranted to elucidate the most effective statin in dogs.…”
Section: Discussionmentioning
confidence: 91%
“… 5 However, in this study, the C max of SIM was reduced 5-fold compared to the reported C max value. 34 The current formulation was designed so that it could release AML-B but withhold release of SIM after about 8 h. Thus, reduction in C max was likely due to its delayed release till 8 h, though further proof is required to substantiate the hypothesis. The in-vitro release data revealed successful achievement of this aim of dosage form development which was supported by the pharmacokinetic study as well.…”
Section: Resultsmentioning
confidence: 99%
“…AUC 0-∞ of SIM in the current study was reduced 2-fold compared to reported values. 34 Immediate release formulations can potentially lead to the saturation of intestinal metabolic enzymes, subsequently leading to an enhanced bioavailability. 35 , 36 SIM is subjected to pre-systemic metabolism mainly by CYP 3A4 located in the enterocytes.…”
Section: Resultsmentioning
confidence: 99%